The EspF N-Terminal of Enterohemorrhagic Escherichia coli O157:H7 EDL933w Imparts Stronger Toxicity Effects on HT-29 Cells than the C-Terminal - Wang, Xiangyu; Du, Yanli; Hua, Ying; Fu, Muqing; Niu, Cong; Zhang, Bao; Zhao, Wei; Zhang, Qiwei; Wan, Chengsong (Frontiers in Cellular and Infection Microbiology, 2017)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 EspF is an important multifunctional protein that destroys the tight junctions of intestinal epithelial cells and promotes host cell apoptosis. However, its molecular mechanism remains elusive. We knocked out the espF sequence (747 bp, ΔespF), N-terminal sequence (219 bp, ΔespFN), and C-terminal sequence (528 bp, ΔespFC) separately using the pKD46-mediated λ Red homologous recombination system. Then, we built the corresponding complementation strains, namely, ΔespF/pespF, ΔespFN/pespFN, and ΔespFC/pespFC by overlap PCR, which were used in infecting HT-29 cells and BALB/C mice. The level of reactive oxygen species, cell apoptosis, mitochondrial trans-membrane potential, inflammatory factors, transepithelial electrical resistance (TER), and animal mortality were evaluated by DCFH-DA, double staining of Annexin V-FITC/PI, JC-1 staining, ELISA kit, and a mouse assay. The wild-type (WT), ΔespF, ΔespF/pespF, ΔespFC, ΔespFC/pespFC, ΔespFN, and ΔespFN/pespFN groups exhibited apoptotic rates of 68.3, 27.9, 64.9, 65.7, 73.4, 41.3, and 35.3% respectively, and mean TNF-α expression levels of 428 pg/mL, 342, 466, 446, 381, 383, and 374 pg/mL, respectively. In addition, the apoptotic rates and TNF-α levels of the WT, ΔespF/pespF, and ΔespFC were significantly higher than that of ΔespF, ΔespFN, ΔespFC/pespFC, and ΔespFN/pespFN group (p < 0.05). The N-terminal of EspF resulted in an increase in the number of apoptotic cells, TNF-α secretion, ROS generation, mitochondria apoptosis, and pathogenicity in BalB/c mice. In conclusion, the N-terminal domain of the Enterohemorrhagic E. coli O157:H7 EspF more strongly promotes apoptosis and inflammation than the C-terminal domain.